Prior Telephone Confirmation to Reduce Absenteeism in Oncological Surgeries: A Phone Call That Saves Lives - Galvão de Souza, Danielly Acioli; Brazorotto, Joseli Soares; Sena, Erika Maria Araújo Barbosa de; Vasconcelos, Talita Lúcio Chaves; Medeiros, Breno Carvalho de; Rêgo, Amália Cinhtia Meneses; Araújo-Filho, Irami (International Journal of Innovative Research in Medical Science, 2019)
In assessing the quality of health services, the use of quality and resolution indicators used in the operating room stands out. The cancellation fee for operating procedures is one of the most important. Cancellations interfere with the outcome of care and increase hospital costs. In the case of cancer patients, the consequences are severe, since early surgical intervention directly influences prognosis, reducing morbidity, and mortality. Considering that surgical suspensions should be prevented, pre-anesthetic consultation and telephone confirmation days before the procedure configure strategies that can be adopted to minimize the problem. A descriptive observational study with a quantitative approach was conducted on the impact of previous telephone confirmation on the reduction of cancellation of oncologic surgeries due to absenteeism. The research was carried out at Professor Alberto Antunes University Hospital, Federal University of Alagoas (HUPAA/UFAL), city of Maceió, State of Alagoas, Northeastern Brazil. The sample consisted of 205 patients with scheduled cancer surgery from January to June 2019, after approval by the Institutional Ethics Committee. Data analysis was performed descriptively. The effectiveness of previous telephone confirmation was verified, with a 50% reduction in cancellation of elective oncologic surgeries due to absenteeism. The implementation of a call center to confirm the presence of the user consisted of an impact strategy in reducing the cancellation of previously scheduled cancer surgeries.